Users' Perception on Collection and Services of the Medical College Libraries in Uttar Pradesh: a Survey - Mahawar, K. L.; Siddiqui, Mohammad Azeem (Journal of Information and Knowledge, 2013)
Medical college libraries are set up in medical colleges to lend support to their basic function of promoting medical education and research. Such libraries are entrusted with the responsibility to develop a good collection of documents comprising of medical literature, which is required and demanded by its users. Moreover, they have to be well equipped to meet all the users’ needs in a wide range of disciplines related to medicine. The medical college libraries have to cater to the needs of medical students, research scholars and faculty cum practitioners.